PENGARUH DIGITAL PAYMENT DAN ONLINE REVIEW TERHADAP NIAT BELI KONSUMEN PADA UMKM GEDONG ROTI DI DENPASAR - Mulia Putra Muliana; Putu Astri Lestari; Gede Puspa; Putu Yogi Agustia Pratama (Berajah Journal, 2026)
This study aims to analyze the effect of digital payment and online reviews on consumer purchase intention at Gedong Roti MSMEs in Denpasar City. A quantitative approach was employed involving 120 respondents selected through purposive sampling. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS version 3.2.9 software. The results indicate that digital payment and online reviews have a positive and significant effect on consumer purchase intention. These findings suggest that the convenience of digital payment systems and credible online reviews can enhance consumers' purchase intentions toward Gedong Roti MSMEs.